2009
DOI: 10.1080/10349120902868632
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Teachers' Ideas about Including Children with Disabilities in Programmes Designed for Typically Developing Children

Abstract: This study examined the influence of information about children's disabilities on preschool teachers' responses toward integrating children with disabilities in their classroom. Of particular interest was whether the severity of the child's educational needs and information about diagnosis were related to teachers' responses. Data were collected from 155 preschool teachers in two Midwest states in the United States to examine their responses in terms of levels of comfort, classroom adaptation, and need for sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 28 publications
3
20
0
7
Order By: Relevance
“…For instance, this Downloaded by [University of Tasmania] at 16:59 27 November 2014 concurs with the results of previous research, which found that teachers' attitudes to inclusion became positive after they received appropriate sensitization and awareness exposure and training in special and inclusive education (Dupoux et al, 2006). In addition, teachers with experience in working with children with disabilities had high comfort levels with inclusive education (Ernst & Rogers, 2009;Huang & Diamond, 2009). No significant differences were found in the attitudes of male and female teachers.…”
Section: Positive Attitudes To Inclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…For instance, this Downloaded by [University of Tasmania] at 16:59 27 November 2014 concurs with the results of previous research, which found that teachers' attitudes to inclusion became positive after they received appropriate sensitization and awareness exposure and training in special and inclusive education (Dupoux et al, 2006). In addition, teachers with experience in working with children with disabilities had high comfort levels with inclusive education (Ernst & Rogers, 2009;Huang & Diamond, 2009). No significant differences were found in the attitudes of male and female teachers.…”
Section: Positive Attitudes To Inclusionsupporting
confidence: 93%
“…The basic concept of inclusion argues against segregation and discrimination of learners in schools (Avramidis, Bayliss, & Burden, 2000). For inclusion to be effective, general education teachers should be receptive to the principles and demands of inclusion to ensure inclusive policies are appropriately implemented and teachers are committed to teach even the most challenging students (Berry, 2010;Hill, 1999;Huang, & Diamond, 2009).…”
mentioning
confidence: 99%
“…Por otro lado, se ha demostrado que los profesores aceptan mejor a los alumnos con discapacidades físicas que psíquicas (Cagran y Schmidt, 2011;Huang y Diamond, 2009;Soodak, Podell, y Lehman, 1998). En este sentido, Aguilera et al (1990) advierten que aquello que más condiciona las actitudes, no es tanto el tipo de déficit sino el nivel intelectual asociado al déficit.…”
Section: Actitudes De Los Profesionales De La Educaciónunclassified
“…In fact, Huang and Diamond (2009) found that there were differences in teachers' attitudes about integrating children with disabilities in their preschool classrooms, depending on the type and severity of disability. However, other researchers (Algozzine et al 1988;Ysseldyke et al 1989) found that teachers did not change their interventions in relation to the child's disability category (i.e., motor disability, blind) or level of severity (i.e., severe or mild disability).…”
Section: Introductionmentioning
confidence: 95%